Does offering small financial incentives to smokers at the time of being wait-listed for surgery increase smoking cessation by the day of surgery? A randomised feasibility trial - Ashley Webb; Lisa Coward; Michael Yousef; Alexandra Karamesinis; Samuel Leong (BMJ Open)
Objective This study aims to assess whether offering small financial incentives to smokers on elective surgery wait-lists is feasible and increases quitting before surgery.Design Randomised controlled trial, prospective, double-blinded.Setting Single-centre, Australian metropolitan public hospital.Participants 620 adult smokers (≥10 cigarettes per day) were randomised on being wait-listed for elective surgery and 404 underwent operations (28 January 2021–31 July 2022) at the hospital (65.2%) by trial’s end.Intervention Intervention participants were offered at wait-listing an $A70 supermarket voucher for verified abstinence on the day of surgery, provided they registered an intention to quit before surgery. Registrants intending to quit were also referred to Quitline. Neither intervention was offered to control participants (usual care). Smokers wait-listed from 17 May 2021 were offered an increased incentive of $A140.Main outcome measures Primary outcome, quitting at least 24 hours before surgery, verified by exhaled carbon monoxide testing. Feasibility outcomes were the proportion taking up offers, ease of patient contact and disputes about quit status.Results Of 620 randomised participants (control 312, intervention 308), 404 had surgery at the hospital during the trial (control 214, intervention 190), which was lower than expected (for COVID-19 reasons). Offering $A70 resulted in 21.9% registering to quit, increasing to 32.6% with $A140. Telephone calls were the most effective means to gain registrations. The proportion of intervention group patients verified quit at least 24 hours before surgery was similar to controls (9.5% vs 8.9%, OR 1.1, 95% CI 0.5 to 2.2). Quitline contact was higher in the intervention group (13.2% vs 2.3%, OR 6.3, 95% CI 2.3 to 21.6). Disputes over test results did not occur, but 17.4% of intervention participants claiming quit failed verification.Conclusion A single offer of financial rewards for perioperative cessation was feasible, without achieving clinically important quit differences.Trial registration number ACTRN12620000130965.